An action research increasing learning outcomes on fractions of 4th Grade students through RME - Yurniwati Yurniwati; Ratih Purnamasari (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The purpose of this study is to improve the performance of grade 4 students infractions through Realistic Mathematics Education (RME). This research was conducted at SDN Cilendek Timur 2 Bogor, Indonesia. The research method used is Classroom Actionresearch with Kemmis and Taggart model, which consists of planning, action, observation,and reflection. This study consists of three cycles. The percentage of students whoachieved fraction score more than or equal to 70 in the first Cycle was 12.5%, in thesecond Cycle was 56.5%, and in the third Cycle was 92%. The activities of teachers andstudents in accordance with the learning steps with RME reach 92.5% at the end of CycleIII. So it can be concluded that RME can improve student learning outcomes in fractions.Also, RME increased students mathematics attitudes